Deletion of NGG1 in a recombinant Saccharomyces cerevisiae improved xylose utilization and affected transcription of genes related to amino acid metabolism - Cheng, Cheng; Wang, Wei-Bin; Sun, Meng-Lin; Tang, Rui-Qi; Bai, Long; Alper, Hal S.; Zhao, Xin-Qing (Frontiers in Microbiology, 2022)
Production of biofuels and biochemicals from xylose using yeast cell factory is of great interest for lignocellulosic biorefinery. Our previous studies revealed that a natural yeast isolate Saccharomyces cerevisiae YB-2625 has superior xylose-fermenting ability. Through integrative omics analysis, NGG1, which encodes a transcription regulator as well as a subunit of chromatin modifying histone acetyltransferase complexes was revealed to regulate xylose metabolism. Deletion of NGG1 in S. cerevisiae YRH396h, which is the recombinant yeast using S. cerevisiae YB-2625 as the host strain, improved xylose consumption by 28.6%. Comparative transcriptome analysis revealed that NGG1 deletion down-regulated genes related to mitochondrial function, TCA cycle, ATP biosynthesis, respiration, as well as NADH generation. In addition, the NGG1 deletion mutant also showed transcriptional changes in amino acid biosynthesis. Further analysis of intracellular amino acid content confirmed the effect of NGG1 on amino acid accumulation during xylose utilization. Our results indicated that NGG1 is one of the core nodes for coordinated regulation of carbon and nitrogen metabolism in the recombinant S. cerevisiae using xylose as the sole carbon source. This work provides novel insights into the function of Ngg1p in yeast metabolism, and provides basis for developing robust yeast strains to produce ethanol and biochemicals using lignocellulosic biomass.